Dexamethasone-conjugated DNA nanotubes as anti-inflammatory agents in vivo. (July 2017) - Sellner, Sabine; Kocabey, Samet; Zhang, Tao; Nekolla, Katharina; Hutten, Saskia; Krombach, Fritz; Liedl, Tim; Rehberg, Markus
Abstract: The biopolymer DNA allows to create nanoscale, biocompatible structures, which can be designed in a target-specific and stimuli-responsive manner. DNA carrier systems with these characteristics hold a great potential for nanomedical applications, such as for the treatment of inflammatory diseases. Here we used a DNA-based drug carrier system for the pH-dependent delivery of the glucocorticoid dexamethasone into macrophages, a cell type with a key role in the regulation of inflammation. Dexamethasone (Dex) nanotubes were internalized within minutes by MH-S macrophages in vitro and by tissue resident macrophages in the mouse cremaster muscle in vivo and localized in their endosomes. Treatment with Dex nanotubes in vitro significantly reduced the LPS-induced TNF secretion by macrophages, as compared to equivalent amounts of free dexamethasone without affecting cell viability. Microinjection of Dex nanotubes into postischemic muscle tissue of anesthetized mice resulted in a marked reduction of ischemia-reperfusion-elicited leukocyte transmigration and diminished vascular expression of the endothelial adhesion molecules VCAM-1 and ICAM-1. Taken together, our results demonstrate that DNA nanotubes can be used as a platform for the targeted delivery of glucocorticoids and could thus foster the development of nanomedical therapeutics with reduced off-target effects.